Influence of concussion history and genetics on event-related potentials in athletes: Potential use in concussion management - Guth, T.; Ketcham, C. J.; Hall, E. E. (Sports, 2018)
Sports-related concussions are an increasing public health issue with much concern about the possible long-term decrements in cognitive function and quality of life that may occur in athletes. The measurement of cognitive function is a common component of concussion management protocols due to cognitive impairments that occur after sustaining a concussion; however, the tools that are often used may not be sensitive enough to expose long term problems with cognitive function. The current paper is a brief review, which suggests that measuring cognitive processing through the use of event related potentials (ERPs) may provide a more sensitive assessment of cognitive function, as shown through recent research showing concussion history to influence ERPs components. The potential influence of genetics on cognitive function and ERPs components will also be discussed in relation to future concussion management.